Social enterprises and commercial companies: converging or diverging realities? - Meira, Deolinda; Ramo, Maria Elisabete (Cooperativismo & Desarrollo, 2019)
This paper discusses the relationship between commercial companies and social enterprises. First, this article identifies and analyses the initiatives taken by the European Union institutions in the field of social enterprises; secondly, it discusses legislative solutions adopted by several Member States; and, finally, it reflects on the Portuguese legal system. Although the European Union has several initiatives aimed at social enterprises, this is a non-harmonized matter. In this context, a number of Member States incorporated specific legislation on social enterprises into their legal systems, but the models of legislation differ, as well as the legal regulation adopted. From the various initiatives of the European Union on social enterprises, it is possible to draw three conclusions: companies can, if certain requirements are met, be considered as social enterprises; the Portuguese legal system does not, expressly and generically, regulate social enterprises; and the creation of hybrid figures designed to accommodate the specific characteristics of social enterprises depends on the Portuguese legislator intervention.